Does the Empowering Function of the Belief in a Just World Generalise? Broad-base Cross-sectional and Longitudinal Evidence - Bartholomaeus, Jonathan; Strelan, Peter; Burns, Nicholas (Social justice research, 2024)
The empowering function of the belief in a just world for the self (BJW-self) has been suggested as one mechanism by which BJW-self promotes positive psychological functioning for the individual. In this investigation we seek to understand if this empowerment function generalises to a broad range of positive and negative psychological variables and whether the function can be observed outside of tightly controlled experimental designs. We use a mix of cross-sectional and longitudinal designs ( N = 840) to test these aspects of the empowerment function. In Sample 1 we find support for the positive indirect effect of BJW-self on life satisfaction, optimism, and resilience through empowerment. Similarly, BJW-self has a negative indirect effect on depression, anxiety, and stress through empowerment. These findings are broadly replicated in Sample 2. A subsample of Sample 1 completed measures again after one year (Subsample 3) allowing for a longitudinal test of the empowerment function. Findings provide mixed support for the empowering contribution of BJW-self to adaptive outcomes over time. Theoretical implications are discussed, as well as the important methodological and measurement issues that require attention for the individual differences study of BJW to progress effectively.